Parents, healthcare professionals and other stakeholders' experiences of caring for babies born too soon in a low-resource setting: a qualitative study of essential newborn care for preterm infants in Kenya. Issue 6 (23rd June 2021) - Mitchell, Eleanor J; Pallotti, Phoebe; Qureshi, Zahida P; Daniels, Jane P; Oliver, Mary; Were, Fredrick; Osoti, Alfred; Gwako, George; Kimani, Violet; Opira, Jacqueline; Ojha, Shalini
Abstract : Objectives: Prematurity is the leading cause of global neonatal and infant mortality. Many babies could survive by the provision of essential newborn care. This qualitative study was conducted in order to understand, from a family and professional perspective, the barriers and facilitators to essential newborn care. The study will inform the development of an early warning score for preterm and low birthweight infants in low and middle income countries (LMICs). Setting: Single-centre, tertiary referral hospital in Nairobi, Kenya. Participants: Nineteen mothers and family members participated in focus group discussions and 20 key-informant interviews with professionals (healthcare professionals and policy-makers) were conducted. Focus group participants were identified via postnatal wards, the newborn unit and Kangaroo Mother Care (KMC) unit. Convenience and purposive sampling was used to identify professionals. Outcome measures: Understanding facilitators and barriers to provision of essential newborn care in preterm infants. Results: From 27 themes, three global themes emerged from the data: mothers' physical and psychological needs, system pillars and KMC. Conclusion: Meeting mothers' needs in the care of their babies is important to mothers, family members and professionals, and deserves greater attention. Functioning system pillars depended on a standardised approach to care and low cost, universally applicable interventions are needed to support the existing care structure. KMC was effective in both meeting mothers' needs, supporting existing care structures and also provided a space for the resolution of the dialectical relationship between families and hospital procedures. Lessons learnt from the implementation of KMC could be applied to the development of an early warning score in LMICs.